2022
DOI: 10.2478/ahem-2022-0016
|View full text |Cite
|
Sign up to set email alerts
|

Salivary HPV infection in healthy people

Abstract: Introduction In recent years, interest in human papillomavirus infections as a causative factor in epithelial cancer development has grown. Literature indicates that HPV involvement in malignant transformations in oral mucosa can vary significantly, from 0 up to 87%. The aim of our study was to detect the prevalence of salivary HPV infection among generally healthy adults. Materials and Methods The examination involved 139 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…In the estimation of p16 INK4A and HSV positivity in connection with the clinical diagnosis, statistical difference was shown among the overgrowth of mucosa samples when referring to the total number of positively diagnosed samples. Data from literature indicate the prevalence of HPV in the oral cavity ranging from 17.7% to 1.0% [ 31 , 41 ]. As described by Paver et al HPV positive squamous cell carcinoma arising in the head and neck region does not carry the favorable prognosis [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the estimation of p16 INK4A and HSV positivity in connection with the clinical diagnosis, statistical difference was shown among the overgrowth of mucosa samples when referring to the total number of positively diagnosed samples. Data from literature indicate the prevalence of HPV in the oral cavity ranging from 17.7% to 1.0% [ 31 , 41 ]. As described by Paver et al HPV positive squamous cell carcinoma arising in the head and neck region does not carry the favorable prognosis [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the infection with HSV and HPV represents the global burden [ 31 ], the aim of this study was to establish the prevalence of p16 INK4A surrogate marker for HPV and HSV in biopsies with the different clinical and histopathological diagnosis, taken from diverse oral mucosa sites, among them OPMD’s.…”
Section: Introductionmentioning
confidence: 99%
“…33 Various HPV-associated diseases in the oral cavity, such as squamous papilloma, verruca vulgaris, condyloma acuminatum, Heck's disease, leukoplakia, lichen planus, and squamous cell carcinoma, do not produce oral vesicles or ulcerations but mainly keratinized verrucopapillary lesions. 34 Currently, COVID-19 remains an overwhelming pandemic throughout the globe. Coincidentally, monkeypox has become spreading out in many non-endemic regions.…”
Section: Discussionmentioning
confidence: 99%
“…Oral leukoplakia, which is the most common multifactorial premalignant lesion of the oral mucosa, may be induced by the inveterate use of tobacco in either smoked or smokeless form [ 114 ]; it has been shown that tobacco users have higher epithelial expression of MMPs, which imply their involvement in tobacco carcinogenesis [ 115 ]. High-risk human papillomavirus (HR-HPV) infection may be another cause of leukoplakia and carcinoma development [ 116 , 117 , 118 ]; HR-HPV E6 and E7 oncoproteins have an impact on cell homeostasis through inactivation of the p53 and pRB tumor suppressors, which leads to cellular immortalization [ 114 ], but it is not enough to explain the occurrence of cancer. Modification of the ECM by MMPs may represent another factor necessary for the establishment and progression of tumors [ 119 ].…”
Section: A Brief Glance At the Role Of Matrix Metalloproteinases In T...mentioning
confidence: 99%